Serodiagnosis of Aleutian Disease Virus Infection in Mink – Short Term Stability and Long Term Consistency of Antibody Levels Measured by VP2 ELISA. Issue 1 (2016) - Andersson, Anna-Maria; Nyman, Ann-Kristin; Wallgren, Per
No abstract available